A genre and collocational analysis of consequence, result, and outcome - Supakorn Phoocharoensil (Penerbit Universiti Kebangsaan Malaysia, 2020)
This corpus-based study examines genres and collocation patterns in which the three synonyms ‘consequence’, ‘result’, and ‘outcome’ usually occur. The data on which the study is based is derived from the Corpus of Contemporary American English (COCA). Of all the eight genres currently available in COCA, the three synonyms appear with the highest frequency in academic texts, whereas frequencies are lowest in informal genres, i.e. TV and movie subtitles and fiction. Of pedagogical concern is the fact that the common verb and adjective collocates repeatedly co-occur with the synonymous nouns. Determined by the COCA frequency and the MI value (≥ 3), ‘consequence’ is often used with verbs and adjectives conveying negative senses, and the typical collocates of ‘result’ has a clear association with research-oriented contexts. The collocates of ‘outcome’ have the broadest variety of semantic properties but are not directly related to any specific contexts. It is highly recommended that EFL teachers apply this genre and collocational information to synonym development lessons.